DETERMINANTS OF INTENTION TO USE MOBILE PERSONAL FINANCIAL MANAGEMENT TOOLS USAGE IN INDONESIA - Akira, Joshua
Personal Financial Management (PFM) is an important aspect that is required to be recognized and understood, especially to Generation Z which will be entering adulthood and work life, it is usually correlates with savings, budgeting, and also planning. The development of financial technology provides help to create more simplified and effective PFM, it even enables people to manage their finance over mobile phones. As PFM may aids the standard of living and reducing poverty, it is important to understand some factors that are believed to have significant influence towards the intention to use mobile PFM tools. To examine it, this study is using a model that combined Technology Acceptance Model (TAM) with Theory of Planned Behaviour (TPB) which have the following variables: Perceived Usefulness, Perceived Ease of Use, Attitude, Subjective Norm, and Perceived Behavioural Control, with two additional variables: Perceived Cost and Compatibility, that will be tested to the variable influence. This study has a scope within Generation Z which perceived to have familiarity with technological usage and also the city of Jakarta, Bogor, Depok, Tangerang, Bekasi, and Bandung. There are 419 questionnaires that are analysed, which is further assessed by using quantitative approach with Structural Equation Modelling (SEM). The result of this study indicates that there are 5 factors that are significant to intention: Perceived Ease of Use, Attitude, Perceived Behavioural Control, Perceived Cost, and Compatibility. The recommendations that are based by the results is given to the application developer, government, and also users, in which it may provide insights and increase the effectiveness of personal financial management